SISTEM PENUNJANG KEPUTUSAN PEMILIHAN HANDPHONE MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Sarifah, Sarifah; Merlina, Nita (LPPM Universitas Nusa Mandiri, 2015)
Decision Support System as a tool in decision making at this time began to be applied in various areas of life, not least in making a decision for the selection of a product. One of them, the choice in the purchase of a mobile product that is now available with a variety of options ranging from the brand, features, and so forth. This triggers the problem for consumers who would buy a mobile product because they feel confused to choose the product that liking, so do not be surprised if consumers sometimes choose the wrong mobile phone that suits their needs because of the plurality of types, specifications, and the price offered. Decision Support System using the method of Analytical Hierarchy Process ( AHP ) is applied to obtain the weights of criteria and alternatives so that the final result with the highest weight value scoring. Thus it is expected to help recommend to consumers in the choice of mobile products that suit, usability and budget